Identification of key factors for enhancing competitiveness: an exploratory study of the selected agri-biotech firms of Punjab in India - Sandeep SINGH; Ravi KIRAN; Dinesh GOYAL (Agricultural Economics (AGRICECON), 2015)
The present study covers empirical research on the selected Agri-Biotech firms of Punjab. The sample has been chosen from the state of Punjab covering the sectors Food Processing Industry, Fertilizer and Pesticides Industry. On the basis of factor analysis, the study has also identified key factors influencing competitiveness. These are Threat of new competition; Threat of substitute products or services; Bargaining power of suppliers; Intensity of competitive rivalry; Bargaining power of customers; Rivalry among existing firms. The study also tries to evaluate the findings on the basis of the author-factor matrix. The aim is to identify the key factors influencing competiveness. It analyses the difference in competitive factors on the basis of the nature of the industry and on the basis of scale of the firms. Then finally it tries to determine the key competitive factors influencing the market share. The results indicate that the Threat of new competition and Threat of substitutes/services emerge as the important predictors. Intensity of competitive rivalry; Preparedness for Competition; and Bargaining power of suppliers also emerge as significant predictors. These variables explain 79.6% of variation in the model.